A Protocol for Development of Holistic-Entrepreneur Graduates: Emotional Intelligence Perspectives - Mohamad, Nurul Haerani; Ibrahim, Badaruddin; Selamat, Asri; Ismail, Affero; Abdul Kadir, Zulida (Journal of Technical Education and Training, 2021)
Entrepreneurship is seen as a potential career path for overcoming the problem of unemployment among TVET graduated especially during this Covid-19 outbreaks. However, this career has yet to get a second or even a last option TVET graduates in Malaysia. Various efforts have been undertaken by the stakeholders through the first surge of the Malaysia Education Blueprint 2015-2025 (Higher Education) and the continuation of the implementation of the Entrepreneurship Action Plan 2016-2020, the holistic development of human capital and entrepreneurial backbone graduate entrepreneurs in targeted delivery. However, based on current achievements, this is not easy to be implemented as the desire of entrepreneurship is not incredibly encouraging, especially graduates in technical and vocational courses. Therefore, this study was conducted to explore emotional intelligence attributes needed by TVET graduates to become a qualified graduated Holistic-Entrepreneur. This study was conducted qualitatively involved three phases. The first phase: data acquisition qualitatively based on document analysis; second phase: focus group discussion and, third phase: experts’ interview. The participants involved are from Ministry of Education and MTUN lecturers and they are expert in students’ development and entrepreneurship. The result shows there are six attributes of emotional intelligence needed by TVET graduates to become a holistic entrepreneur graduates. The implication of the proposed as guideline for relevant parties and TVET graduates in increasing student minded and desire towards entrepreneurship.